Peningkatan Hasil Belajar Bahasa Indonesia Pada Materi Teks Drama Siswa Kelas VIII SMPN 56 Plg Melalui Metode Role Playing - Edwin, Muhammad (SJEE (Scientific Journals of Economic Education), 2025)
This Classroom Action Research aims to improve process skills in applying concepts and acting and improve the learning outcomes of students of SMPN 56 Palembang, in Indonesian language subjects in order to obtain a predetermined minimum score of 76 and 80% reach the KKM score. This Classroom Action Research uses the Role Playing model. The type of research used is Classroom Action Research (PTK) using the Kemmis and Taggart design. Through 2 cycles starting from planning, implementation, and reflection. The participants who became the subjects in this study were class VIII 10 students totaling 30 people consisting of 18 female students and 12 male students. Data collection tools using tests and observation sheets. The results of data processing from observations of each meeting in cycles I and II and student learning outcomes obtained through tests at the end of cycles I and II show that there is a significant increase in student activeness.